Evaluasi User Experience Pada Game Playerunknowns Battleground Mobile Menggunakan Game Experience Questionnaire - Iwan Prasetiyo Hakiki; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Playerunknowns Battleground Mobile is mobile version from game with same name which first realease on PC or Steam platform. Is a popular game today, with a total downloader of more than 100 million people. As time goes by, similar games that became rivals of PUBG Mobile began to emerge. To maintain the popularity, PUBG Mobile an evaluation needs to identify the weakness and advantages of PUBG Mobile from user experience side and weakness that have been identified can be repaired to increase attractiveness. The result of the evaluation can also be used as reference material in developing a game. This time, many evaluation methods that can be used, one of them is Game Experience Questionnaire, an evaluation method that designed to evaluate user experience in game. Based on the evaluation results, PUBG Mobile has disadvantage in competence aspect in non-gamer group and return to reality aspect in non-gamer and gamer group.